Hubungan Antara Preeklamsia Berat Dengan Kejadian Bayi Berat Lahir Rendah (BBLR) Di RS Dr. Oen Surakarta - Utami, Ummi, Dr. Supanji Raharja, Sp.OG (K) (2017)
Background: Preeclampsia is one of three main causes of maternal mortality. Based on the degree of severity, Preeclampsia are classified into mild and severe preeclamsia. Severe preeclampsia causes maternal mortality and morbidity as well as lead to hypoperfusion in the uteroplacental circulation, which can lead to babies born with low birth weight Objective: This study was conducted to determine the relationship between severe preeclampsia and the incidence of low birth weight in Dr. Oen Hospital Surakarta Methods: This study used analytic observational study design with cross-sectional approach. The samples used were 110 samples of pregnant women in Dr. Oen Hospital Surakarta taken with purposive sampling techniques. The data is analyzed using the chi-square test. Results: From 110 samples, 55 mothers who experience severe preeclampsia 20.9% gave birth to low birth weight and 55 mothers without preeclampsia only 6.4% give birth to low birth weight.Statistical test results between severe preeclampsia and the incidence of low birth weight babies are p 0.001 and RP 3.29. Conclusion: There is a significant relation between severe preeclampsia and the incidence of low birth weight in Dr. Oen Hospital Surakarta. Keywords: Preeclampsia, Severe Preeclampsia, Low Birth Weight